The value of ultrasonography in the diagnosis of early cirrhosis* - , Galip ERSÖZ, Ulus Salih AKARCA, Funda YILMAZ, Ömer ÖZÜTEMİZ, Zeki KARASU, Tankut İLTER (Turkish Journal of Gastroenterology 1, 2019)
-